TOURISM INDUSTRY DEVELOPMENT IN THE CONTEXT OF THE CORONAVIRUS (COVID-19) PANDEMIC: RESPONSE AND RECOVERY MEASURES - Abdulkadirov, Umalt; Biryukov, Vladimir; Yudina, Elena (Revista Inclusiones, 2020)
The article analyzes the impact of the COVID-19 pandemic on the tourism industry. Based on an expert survey, the necessary response measures have been defined to restore the functioning of the tourism industry, including support for tourists and tourism workers, support for tourism companies and destinations, coordination measures, as well as measures to restore confidence and demand stimulation. It has been proven that in order to overcome the negative consequences of the coronavirus pandemic in the tourism sector, it is necessary to take appropriate measures to mitigate the consequences of the pandemic, with their subsequent transformation into longer-term measures to restore and stimulate the functioning of the tourism industry.